2013
DOI: 10.1002/ptr.4954
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNF‐α‐Induced MUC5AC Mucin Gene Expression and Production by Wogonin Through the Inactivation of NF‐κB Signaling in Airway Epithelial Cells

Abstract: In this study, we investigated whether wogonin significantly affects MUC5AC mucin gene expression and production in human airway epithelial cells. Confluent NCI-H292 cells were pretreated with wogonin for 30 min and then stimulated with tumor necrosis factor-α (TNF-α) for 24 h or the indicated periods. The MUC5AC mucin gene expression and mucin protein production were measured by RT-PCR and ELISA, respectively. We found that incubation of NCI-H292 cells with wogonin significantly inhibited mucin production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…This study first demonstrates that flavones have anti-inflammatory effects on Muc5AC and iNOS up-regulation as well cytokine secretion in airway epithelial cells. This supports prior studies that apigenin, chrysin, and wogonin inhibit Muc5AC up-regulation in NCI-H292 bronchial cancer cells in response to epidermal growth factor (91,112,113) or TNF␣ (114,115). Our data suggest this occurs partly through direct inhibition of kinase C rather than upstream or downstream mechanisms, as they were directly able to block PKC activity in response to PMA.…”
Section: Discussionsupporting
confidence: 92%
“…This study first demonstrates that flavones have anti-inflammatory effects on Muc5AC and iNOS up-regulation as well cytokine secretion in airway epithelial cells. This supports prior studies that apigenin, chrysin, and wogonin inhibit Muc5AC up-regulation in NCI-H292 bronchial cancer cells in response to epidermal growth factor (91,112,113) or TNF␣ (114,115). Our data suggest this occurs partly through direct inhibition of kinase C rather than upstream or downstream mechanisms, as they were directly able to block PKC activity in response to PMA.…”
Section: Discussionsupporting
confidence: 92%
“…Also, two of their components-wogonin and apigenin-were reported to have various biological effects including antiinflammatory effect9,10,11,12,13,14,15. In our previous study, wogonin inhibited tumor necrosis factor α-induced MUC5AC mucin gene expression and production through the inactivation of nuclear factor-κB signaling in airway epithelial cells16. Also, we demonstrated that wogonin or apigenin inhibited epidermal growth factor (EGF)- or phorbol myristate acetate-induced MUC5AC mucin production and gene expression17.…”
Section: Introductionmentioning
confidence: 91%
“…Also, apigenin was isolated as the active component from Selaginellae Herba ( Selaginella tamariscina Spring, Selaginellaceae), the major medicinal plant of Pyunkang-hwan (Pyunkang-tang), an herbal medicinal preparation used for controlling the hypersecretion of airway mucus observed in bronchitis, tonsiltis and pneumonitis in folk medicine (unpublished data). In our previous study, we demonstrated that apigenin inhibited epidermal growth factor (EGF)- or phorbol 12-myristate 13-acetate (PMA)-induced MUC5AC protein and gene expression ( Kim et al ., 2012 ) and wogonin, another flavonoid, affected TNF-α-induced NF-κB signaling pathway in MUC5AC mucin producing NCI-H292 cells ( Sikder et al ., 2014 ). However, to the best of our knowledge, there are no reports about the potential effect of apigenin on mucin gene expression and production stimulated by a proinflammatory cytokine, TNF-α, from airway epithelial cells.…”
Section: Introductionmentioning
confidence: 99%